NEUROTROPIC PROPERTIES OF RETROVIRUSES IN THE CONTEXT OF ANXIETY-DEPRESSIVE AND COGNITIVE DISORDERS IN HIV-POSITIVE PATIENTS - Chemych, Mykola; Sosnovenko, Dmytro (Eastern Ukrainian Medical Journal, 2024)
The aim: a comprehensive assessment and comparison of the prevalence of undiagnosed anxiety-depressive and cognitive symptoms in HIV-positive individuals at different stages of the disease who have been undergoing treatment for an extended period. Materials and methods According to the criteria of the scientific project, 71 HIV-positive individuals undergoing outpatient treatment with a compensated condition were involved. To explore dependencies on clinical stages (ClSt) of HIV infection and search for gender differences, the study was divided into 2 stages, respectively. The research included the collection of epidemiological and clinical-anamnestic data, as well as laboratory studies. Clinical-psychopathological and psychometric methods were used. Inclusion criteria for the study were HIV-positive status, receiving ART for more than 6 months, adulthood, and voluntary consent to participate. The obtained information was statistically processed by mathematical methods of statistics, using ANOVA criteria, Student’s t-test, etc. Elements of neurocognitive and anxiety-depressive symptomatology were considered, utilizing GAD-7, HADS, and MMSE scales. Results: In patients of different groups in the first stage of the study, a gradually increasing level of anxiety and cognitive impairments was identified, depending on the stage of HIV infection. In the second stage of the study, gender and stage-related differences in anxiety and cognitive disorders were found in patients of all groups. Conclusions. Individuals in the first clinical stage (I ClSt) exhibited the least anxiety-depressive and cognitive disorders, indicating emotional and cognitive stability at this stage of HIV infection. HIV-infected individuals in the second and third clinical stages (II and III ClSt) demonstrated a progressive tendency toward anxious and depressive disorders, indicating a stage-dependent relationship to the progression of the disease. Patients in the fourth clinical stage (IV ClSt) showed the most pronounced anxious, depressive, and cognitive symptoms, which may be associated with the duration of the illness and antiretroviral therapy (ART). Research results in the female group (Group A1) suggest their lower susceptibility to disorders compared to males (Group A2) in the early stages of HIV infection. In the later stages (III-IV), it was found that women had pronounced anxious and depressive disorders (Group B1), while men exhibited signs of cognitive and depressive disorders (Group B2).